The tourism sector: research on tourist prefered destinations and activities in Sabah / Vun Fah Justin - Justin, Vun Fah (2009)
Traverse Tours Sdn Bhd started in 1995. It's popular with it the name Riverbug. The company has grown from just a small company until being the leading name in it's field and continues to operates in the tourism industry. Riverbug has operated for a long time, and had been given the title 'The White Water Rafting Specialists' in Sabah. This is due to the White Water Rafting experience, specialty and professional. This all contributed to how their satisfied clients voted them as Malaysia's number one White Water Rafting operator. The RIVERBUG's crew consists of professional tourist's river guides with more than 10 years of experience in adventure activities, with proficiency in both, Swift Water Rescue Program and White Water Safety. The guides are certified by the New Zealand Canoeing Association. At present, Riverbug rafting crew consists of 50 staff which can handle 300 people in a single journey and at any given time. The crew is the main assets that this company has. Their adventure activities namely; white water rafting, kayaking, corporate training, jungle trekking, wildlife close up, nature adventure, diving, snorkeling and camping.